Immediate electrical storm of Torsades de Pointes after CRT‐D implantation in an ischemic cardiomyopathy patient. Issue 3 (28th November 2014) - Kaya, Adnan; Sungur, Aylin; Tekkesin, Ahmet Ilker; Turkkan, Ceyhan; Alper, Ahmet Taha
Abstract: Cardiac resynchronization therapy with an implantable cardioverter‐defibrillator (CRT‐D) is the preferred treatment for patients with severe heart failure, dyssynchrony, and an increased risk of sudden cardiac death or for primary ventricular arrhythmia survivors. Rarely, left ventricular epicardial pacing can induce ventricular tachyarrhythmia rather than a beneficial effect. We describe an ischemic cardiomyopathy patient who underwent CRT‐D therapy and developed sustained torsades de pointes (TdP) immediately after switching to biventricular pacing (BVP) mode. Here, TdP possibly developed owing to the change in the dispersion of repolarization of the left ventricle myocardium. The diagnosis and management of BVP‐induced ventricular arrhythmia is discussed.